Cybersecurity and cyber terrorism - in energy sector – a review. Issue 3 (2nd October 2018) - Venkatachary, Sampath Kumar; Prasad, Jagdish; Samikannu, Ravi
ABSTRACT: The rapid rise in technological development in various areas in communication, supply chain management, integration of various power resources that are essential and part of critical infrastructure, has brought out new security challenges. This has resulted in securing critical consumer profile and data, operations. Security is not limited to the four walls of the production or generation environment but goes beyond it. As, electric power systems comprise of both IT and power, their interdependence has resulted in gaps in the security. Cyber threats can only be mitigated, reducing its impact but cannot be eliminated. The cyber threat mitigation results in huge expenditure, efforts, downtime, economic and psychological impacts on the industry that could result in damage to company's performance and the national economies. The paper aims to highlight various security attacks on the energy infrastructure and its impacts. While discussing the impacts, the paper presents mechanism and emphasises the need for global security coordination be to mitigate threats. Abbreviation : IoT: Internet of Things; EI: Energy Infrastructure; DER: Distributed Energy Resources; SCADA: Supervisory Control and Data Acquisition; VPN's: Virtual Private Networks; PKI: Public Key Infrastructure; IDS: Intrusion Detection Systems; EMP: Electromagnetic Pulse; MTU: Master Terminal Unit; RTU: Remote Terminal Unit; ICS: Industrial Control Systems; RAT: Remote Access Trojan